Bimbingan Kelompok Untuk Pengembangan Sikap Disiplin Mahasiswa Dalam Kegiatan Kepramukaan - Assaffa, Putri Alfitriany; Muksin, Ucin; Saepulrohim, Asep (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2024)
A number of students still experience obstacles in developing a disciplined attitude, such as lack of motivation, difficulty overcoming lazy tendencies, challenges in managing time effectively, and lack of empathy towards others. In the modern era, students often do not fully realize the importance of discipline, and even experience difficulty in honing themselves in this regard. The aim of this research is to find out the factors that cause indiscipline, to find out the development of students' disciplinary attitudes, and how group guidance services work. This study used a descriptive qualitative method. The results of this research show that, group guidance for developing students' disciplinary attitudes in scouting activities, this can be seen from the administrators and active members of the UIN Sunan Gunung Djati Bandung Scout Movement who have applied a disciplinary attitude.